Foreign Workers and Remittance Outflow in Malaysia - Mat Rawi, Fauziana Bt Fauzi (Information Management and Business Review, 2024)
This conceptual paper reviews foreign workers and remittance outflows in Malaysia. Foreign workers in Malaysia, who remit a portion of their earnings back home, play a crucial role in the country’s economic development. With approximately 1.5 million foreign workers engaged in various sectors such as manufacturing, plantation, construction, and agriculture, Malaysia relies heavily on foreign labor. Predominantly, these workers come from Indonesia, Nepal, and Bangladesh. Factors such as Malaysia’s economic performance, government recruitment policies addressing labor shortages, and cultural and geographical proximity influence why these workers choose Malaysia. Despite concerns that foreign workers might negatively impact short-term labor market outcomes by taking jobs from locals and suppressing wages, the evidence suggests their presence does not significantly harm these outcomes. However, the growing number of foreign workers has led to a notable increase in remittance outflows. Remittance outflows represent a transfer of capital from host countries to the workers’ countries of origin. Among the ASEAN-5 countries, Malaysia has recorded the highest remittance outflows, surpassing inflows. While research on remittance flows has expanded, the focus has traditionally been on inflows, with outflows receiving less attention due to their relatively small impact on the macroeconomic indicators of sending countries. Existing literature indicates that remittance outflows can influence the economic growth and inflation of sending countries, including Malaysia, despite varied findings.